The Development of Non Tax State Revenue Potency by Applying the Logical Framework Approach : A Case Study of Nagrak Research Station in Bogor District, West Java - Wisudayati, Tri Astuti; Hidayat, , Dian Charity; Sudrajat, Dede J. (Jurnal Penelitian Kehutanan Wallacea, 2019)
The Indonesian government strives to increase non-tax state revenues (PNBP). One of the potentials PNBP is using the state assets, such as research stations,for the public interest. This paper was aimed to formulate a strategy for the PNBP potential development using the Logical Framework Approach (LFA), with a case study at the Nagrak Research Station, Bogor. In order to avoid the failure when the PNBP potential development’s stages are implemented, policy makers need to build a hierarchy based on logical thinking of input, activity, output, impact, objectives and summarized them in a work plans matrix. The process of LFA development starts with the analysis of problems, goals,and strategies. Data and information were obtained through participant observation and documentation studies. The results showed that the commercialization of the operational units of research quality’ s seeds and seedlings at the Nagrak Research Station must be supported by the government policy, including: (1) planning of seed and seedling production with the consideration of price competitiveness (2) seeds and seedling production with the financial management flexibilities, and (3) seeds and seedling distribution with stakeholders protection from the non-quality seeds and seedling’s utilization.